A new species of Goeldichironomus Fittkau, 1965 from Argentina (Chironomidae, Chironominae) - Donato, Mariano; Andersen, Trond (Zootaxa, 2022)
Goeldichironomus pampeanus n. sp. is described and figured as male, pupa and larva based on reared specimens from Buenos Aires province in Argentina. The species can be separated from its congeners on the combination of the following characters: male without dark markings on thorax and an evenly curved superior volsella projecting mesad; pupa with extensive shagreen on tergites II–VI, sternites with fine shagreen only without transverse bands of points, dorsal setae on tergite IX extending beyond anal lobe and basal ring of thoracic horn kidney-shaped; larva with bifid premandible, mentum with 6 pairs of lateral teeth, anterior pair of ventral tubules simple, labral sclerite 1 intact and labral sclerite 2 consolidated on the inner side.